THE TRANSFORMATION OF METHODS OF EPISTEMOLOGY INVESTIGATION IN THE PROCESS OF THE APPEARING THE INFORMATIONAL SOCIETY - Кунденко, Я. Н.; Старикова, Г. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article is devoted to the problem of modernization the methodological apparatus of the modern epistemology. The specific of the radical constructivism as one of the direction for decision of this problem is analyses in the article.